Peningkatan Hasil Belajar Siswa Melalui Pendekatan Keterampian Proses Sains (KPS) Pada Tema 9 Siswa Kelas V SDN 015 Samarinda Tahun 2017/2018. - Muhammad Ikhsan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
The purpose of this study was to determine the improvement of student learning outcomes through the approach to science process skills. This research was conducted at SDN 015 Samarinda in 2017/2018 learning year. This research was conducted in class V of SDN 015 Samarinda. Research methods use classroom action research with research instruments, namely Learning Implementation Plans, Test Sheets, Student Sheets and Observation Sheets. Learning outcomes measured include cognitive and student skills. Based on the results of the description test and skill sheet students obtained in cycle 1 the average student score of 67.5, out of 32 students there were 14 students or 43% students who passed the minimum review criteria and 18 students who did not pass the minimum review criteria, with minimum review criteria students 70. This was due to still lack of learning activities involving student skills. In Cycle 2, the teacher makes improvements to the learning cycle 1, the teacher guides students in an activity that can train students' skills through simple practical activities with objects around, so students through activities can think critically to answer problems students' science problems. In learning in cycle 2, there was an increase in the average student score of 78.5 and 29 students or 90.6% of students reached minimum review criteria. Thus, the learning outcomes of Grade V students of SDN 015 in the 2018/2019 learning year can be improved through the Science Process Skills Approach.